ADJUVANT TREATMENT POSSIBILITY OF OZONE THERAPY AND HYPERBARIC OXYGEN IN COVID-19 PATIENTS: A SYSTEMATIC REVIEW - Jason (International Journal of Innovations in Engineering Research and Technology, 2021)
Among various potential treatments, ozone treatment and hyperbaric oxygen therapy towards COVID-19 appears to have an immunological job in view of the regulation of cytokines and interferons, including the acceptance of gamma interferon. Some information propose the conceivable part of ozone treatment in SARS, either as a monotherapy or, all the more everything being equal, as a subordinate to standard treatment regimens; thusly, there is expanding interest in the job of ozone treatment in COVID-19 treatment.